Case report: First case of neuromelioidosis in Europe: CNS infection caused by Burkholderia pseudomallei - Dimitriou, Nikolaos G.; Flüh, Greta; Zange, Sabine; Aytulun, Aykut; Turowski, Bernd; Hartung, Hans-Peter; Meuth, Sven G.; Gliem, Michael (Frontiers in Neurology, 2022)
Neuromelioidosis is a rare CNS-infection caused by Burkholderia pseudomallei that is characterized by high morbidity and mortality. Our report presents the diagnostic and therapeutic approach of the first case of neuromelioidosis confirmed in Europe. A 47-year-old man with a medical history of recurrent otitis with otorrhea and fever after a tympanoplasty and radical cavity revision operation on the left ear was admitted with headache, decreased level of consciousness, dysarthria as well as left-sided hemiparesis and urinary incontinence. After extensive investigations including MRI, microbiological, serological, CSF investigations and ultimately brain biopsy the diagnosis of neuromelioidosis was established. Despite antibiotic treatment the patient showed no clinical improvement and remained in a severe compromitted neurological state under mandatory mechanical ventilation. Neuromelioidosis can provide a diagnostic challenge requiring an extensive diagnostic evaluation due to its uncommon clinical and radiological presentation. Early identification of the pathogen and appropriate antibiotic administration may significantly reduce neurological morbidity and prevent mortality.